Design and Synthesis of Tetrahydrobenzo[4,5]Thieno[2,3-d]Pyrimidine-Sulfonamide Derivatives Using p-Phenylenediamine as a Linker - Akhtar, Ayesha; Chaudhari, Tohasib Yusub; Inam, Afreen (Synthesis, 2025)
Cancer is one of the deadliest causes of death around the globe despite significant advancements in cancer drugs. The development of effective chemotherapy to suppress cancer cells has become a necessity due to off-target side effects. This study outlines the synthesis of a series of tetrahydrobenzo[4,5]thieno[2,3-d]pyrimidine-sulfonamide conjugates M1–M10 using the Gewald reaction. The synthesized derivatives were validated through FT-IR, 1H NMR, and 13C NMR spectroscopy. All the compounds were evaluated for their anticancer activity against the breast cancer cell line (MCF-7). M6 demonstrated a significant IC50 value of 4.61 μM against the breast cancer cell line. Furthermore, in silico studies, ADMET prediction, molecular docking, and MD simulation supported the pharmacokinetic profile and binding interaction with the VEGFR-2 inhibitor. Hence, all results indicate that these derivatives may be considered for further lead optimization in the development of potential anticancer drugs.
Keywords: MTT assay; Thienopyrimidine; p-Phenylenediamine; Sulfonyl chloride; Molecular docking